THE GROWTH RATE OF CELERY (Apium graveolens L.) AT VARIOUS COMPOSITIONS OF ORGANIC AND SYNTHETIC FERTILIZER - Ghani Hendrika; Arifah Rahayu; Yanyan Mulyaningsih (Universitas Djuanda Bogor, 2017)
This study was aimed at assessing the growth and production of celery plants grown with various compositions of N,P and K fertilizer and compost. The study was done at the Trial Farm of Faculty of Agriculture, Djuanda University, Bogor ﬁom September to November 2015. A completely randomized design with two factors was used. The factors consisted of compost rate and N,P and K fertilizer rate. Compost was given in four levels, namely no compost (0% R), 26.3% gcompost/plant (50% R), 52.5 g compost/plant (100% R), and 78.7 g compost/plant (150% R). N, P and K fertilizer was given in ﬁve levels, namely no fertilizer (0% R), 4 g Urea, 0.3 g SP-36, 0.2 g KCl (25% R), 0.9 g Urea, 0.6 g SP-36, 0.4 g KCI (50% R), 1.3 g Urea, 0.8 g SP-36, 0.6 g KCl (75% R), and 1.7 g Urea, 1.1 g SP-36, 0.8 g KCl (100% R). All fertilizers were administered gradually at the time of planting and 2 weeks after planting. Three replicates were allocated into each treatment making up 60 experimental units. Results showed that celery plants given synthetic fertilizer at 100% R had higher plant height, number of leaves, number of seedlings, harvest fresh weight (g), saleable fresh weight (g), root biomass (g), and root dry weight (g) than those treated with no fertilizer (0% R). Plants treated with 150% compost had higher plant height, number of leaves, harvest fresh weight (g), saleable fresh weight (g), root length (cm), and root dry weight (g) than those treated with no fertilizer (0% R). Thus the best celery growth and production in this study was obtained on plant 150% R compost and 100% R synthetic fertilizer nourished.Key words: celery, compost, N, P, K fertilizer, harvest ﬂesh weight